SERAT MENYURI: ANALYSIS OF THE SOCIAL FUNCTION FOR THE KASEPUHAN KEJAWEN KALITANJUNG INDIGENOUS COMMUNITY - Exwan Andriyan Verrysaputro; Idah Hamidah; Rosyid Dodiyanto; Tri Asiati (RADJA PUBLIKA, 2025)
This study aims to describe the social function of the Serat Manyuri Javanese manuscript for the Kejawen Kasepuhan Kalitanjung community in Tambaknegara, Rawalo, Banyumas Regency. This research is categorized as qualitative research. Data were collected through library research and interviews. The data were then analyzed using traditional philological methods, including determining the research focus, manuscript inventory, preliminary observation, and manuscript transcription. Based on the conducted research, several conclusions can be drawn. The moral values in the Serat Manyuri Javanese Manuscript remain relevant to the Kejawen Kasepuhan Kalitanjung community, who are the cultural custodians of this tradition. The traditions practiced by the Kejawen Kasepuhan Kalitanjung community that are related to the use of the Serat Manyuri include: 1) Selametan Kematian Telung Dina lan Pitung Dina Traditions ; 2) Selametan Matang Puluh Dina lan Nyatus Tradition; and 3) Selamten Mendhak Pisan, Pindho, lan Nyewu Traditions. The Serat Manyuri is one of the ancient Javanese manuscripts found in Banyumas, containing numerous moral values that continue to be utilized by the community as a medium in the implementation of traditional ceremonies.